Utilization of information technology for MSMEs to increase competitiveness in the era of society 5.0 in Sumpang Binangae Village - Aulyah Zakilah Ifani; Fitryani Fitryani; Nurani Nurani; Nurul Istiqamah; Andi Widiawati; Eka Wijaya Paula; Agunawan Agunawan (Community Empowerment, 2024)
MSMEs in Indonesia are one of the sources of employment for the community. The training and mentoring in Sumpang Binangae Village, Barru Regency, aims to improve the skills of MSME actors in information technology, e-commerce, and financial management. Thirty MSME participants were given an understanding of the use of technology platforms to develop MSME products and increase their income. The method of implementing activities includes preparation, problem solving, implementation, as well as monitoring and evaluation. The result achieved is that MSME actors are able to utilize technology platforms to promote their goods and services.